The Urban Rehabilitation of Medinas : The World Bank Experience in the Middle East and North Africa - Bigio, Anthony G.; Licciardi, Guido (World Bank, Washington, DC, 2014)
The paper presents the key objectives for the rehabilitation of historic centers or medinas in the Middle East and North Africa as elaborated by the World Bank on the basis of twenty years of past and present lending and technical assistance operations to the governments of the region. These are: 1) the conservation of the urban and cultural heritage; 2) the local economic development of the historic city; and 3) the improvement of the living conditions of the resident population. The paper presents some innovative ways to classify the contemporary users of the medinas into different catagories which then become the market segments to reach via the rehabilitation initiatives given the readically changed present role of historic cities as urban cores of much larger urban agglomerations.The paper reviews the financial and fiscal instrucments that can be used to mobilize the necessary resources, including the roles of scaled up private sector investments and of internaitonal development financing in support of national and local governments. As sustainale culutral tourism I sput forth as the main economic rationale for investment of financial reosurces in medina rehabilitation, the paper also presents an innovative multi-vriteria index to determine the tourism potential of historic cities in the region, which has been recently used in the case of Morocco for a national strategy for the rehabilitation of its historic cities.